Advancing School Professionals’ Dyslexia Knowledge Through Neuroscience: Bridging the Science-Education Gap Through Developmental Psychology - Anderson, Alida (Frontiers in Education, 2021)
This review presents a summary of the research on advancing dyslexia knowledge among school professionals. It contributes to the literature with a proposed solution for professional development and teacher training through the field of developmental psychology. The article outlines what has been done to address the science-education gap owing to misunderstandings about dyslexia, proposing a solution to advance school professionals’ knowledge of dyslexia through developmental psychology coursework aimed at the neuroscience of dyslexia, including basic and cognitive neuroscience concepts. The review outlines the legislative and research support for this proposal as well as the candidate knowledge focused on the neuroscience of dyslexia to address gaps in professional knowledge and practice. The review includes a discussion section with implications for research and practice.